Recent Advances in Technologies for Analyzing Protein Kinases - Atsuhiko Ishida; Isamu Kameshita; Noriyuki Sueyoshi; Takanobu Taniguchi; Yasushi Shigeri (Elsevier, 2007)
Most cellular events are regulated by protein phosphorylation mediated by protein kinases, whose malfunction is involved in the etiology of various disorders. The elucidation of the biochemical properties of the protein phosphorylation reaction will lead not only to a better understanding of the signal transduction mechanism, but also to developing new therapeutic agents. In this review, we briefly summarize the technologies to detect or characterize protein kinases with special emphasis on recently developed and/or commercially available techniques. Keywords:: protein kinase, assay, method, high-throughput screening, proteomic analysis